1999
DOI: 10.1126/science.284.5420.1664
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Cloning of Aggrecanase-1: A Member of the ADAMTS Family of Proteins

Abstract: We purified, cloned, and expressed aggrecanase, a protease that is thought to be responsible for the degradation of cartilage aggrecan in arthritic diseases. Aggrecanase-1 [a disintegrin and metalloproteinase with thrombospondin motifs-4 (ADAMTS-4)] is a member of the ADAMTS protein family that cleaves aggrecan at the glutamic acid-373-alanine-374 bond. The identification of this protease provides a specific target for the development of therapeutics to prevent cartilage degradation in arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
476
0
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 658 publications
(493 citation statements)
references
References 26 publications
11
476
0
5
Order By: Relevance
“…The aggrecanases ADAM-TS4 and ADAM-TS5 are considered to be the principal proteinases responsible for cartilage proteoglycan degradation, and these enzymes contain the typical furin recognition motif (9,10). This study shows that the addition of a furin inhibitor to resorbing cartilage can partially block the breakdown of the proteoglycan matrix.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The aggrecanases ADAM-TS4 and ADAM-TS5 are considered to be the principal proteinases responsible for cartilage proteoglycan degradation, and these enzymes contain the typical furin recognition motif (9,10). This study shows that the addition of a furin inhibitor to resorbing cartilage can partially block the breakdown of the proteoglycan matrix.…”
Section: Discussionmentioning
confidence: 79%
“…MT1-MMP, MT3-MMP, and MMP-11 can all be activated by furin (31)(32)(33). In addition, the aggrecanases ADAM-TS4 and ADAM-TS5 contain this furin cleavage site (9,10), and the pro-domain of ADAM-TS4 can be removed by furin (34). Furin has been detected in normal cartilage, and elevated levels are found in osteoarthritic cartilage (35).…”
mentioning
confidence: 99%
“…The same study also showed upregulation of the aggrecanases ADAMTS-4 (aggrecanase-1) and ADAMTS-5 (aggrecanase-2) by IL-1. These proteins belong to the disintegrin and metalloprotease with thrombospondin motifs family (61), and are the only enzymes that have been shown to cleave aggrecan at a site that generates the Glu373-Ala374 fragments (62,63) seen in interleukin-1 stimulated bovine explant cultures (64) and human synovial fluid of OA patients (65).…”
Section: Models Of Osteoarthritis In Articular Cartilagementioning
confidence: 99%
“…However, 2 defined sites in the interglobular domain are thought to play an important role in normal and OA cartilage (8,9): the so-called MMP site (Asn 341 -Phe 342 ) (10), at which cleavage by many MMPs and in particular stromelysin (MMP-3) is described (10)(11)(12), and the so-called aggrecanase site (Glu 373 -Ala 374 ) (13)(14)(15)(16). For the latter site, enzymes such as aggrecanase 1 (ADAM-TS4) (17,18) and aggrecanase 2 (ADAM-TS5) (19), as well as MMP-14 (20) and more recently ADAM-TS1 (21), are thought to be responsible. At least, all these enzymes have been shown to cleave aggrecan correspondingly and to be expressed in articular chondrocytes in vivo or in vitro (22,23).…”
mentioning
confidence: 99%